ETIKA KRISTEN MENJADIKAN UMAT YANG BERINTEGRITAS - Intan Suriyanti; Steven (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2022)
Ethics and integrity are two things that cannot be separated. People who are know work ethics and do it with all their heart, can be ascertained as a person of integrity. As Christians, the Bible as the word of God and Jesus Christ as an example are the foundation of Christian ethics. In this case, ethics is considered as a means of orientation for human efforts to live and act. For Christians living in Indonesia with its various diversity is challenging, living as the light and the salt is a must to be able to witnessing the truth of God's Word. So that all those who do not know and not interested in knowing Him can be changed into His followers. The truth of God's word can be seen clearly, if someone has and know Christian ethics and live with it. This ethic which refers to the lifestyle of followers of Christ and His Word is the standard for Christian morals and lifestyle. And when they do it honestly and righteously they can be called Christians with Integrity. At the end of 2020, the GBI church under the guidance of Pastor Niko Njotoraharjo declared 2021 as the